AN ECOLOGICAL MONITORING STUDY IN RELATION TO PLANKTON AND BENTHOS IN YUMURTALIK GULF (MEDITERRANEAN SEA, TURKEY) - (:unkn) unknown (Севастополь: ЭКОСИ-Гидрофизика, 2016)
This study was performed in coastal water of Yumurtalık Bay along Mediterrenean coast. In accordance with the goal of the study four stations were determined. Water and phytoplankton samples from 5 and 10 m depths through water bottle and plankton net were collected. Macrophytes, mollusc and porifera species were collected from bottom by means of a grab. Species composition of phytoplankton, macrophyte, mollusc and porifera communities were determined. A total of 31 phytoplankton, three macrophyte, 17 mollusc and one porifera taxa were recorded. The occurrence of toxic diatoms Nitzschia longissima, Pseudo-nitzschia delicatissima, Pseudo-nitzschia pseudodelicatissima, Pseudo-nitzschia lineola were noticable.
ЭКОЛОГИЧЕСКИЙ МОНИТОРИНГ ПЛАНКТОНА И БЕНТОСА В ЗАЛИВЕ ЮМУРТАЛЫК (СРЕДИЗЕМНОЕ МОРЕ, ТУРЦИЯ)
Исследования выполнены в прибрежных водах залива Юмурталык на побережье Средиземного моря. На четырех станциях, определенных в соответствии с целью исследований, отобраны пробы воды и фитопланктона на глубине 5 и 10 м с помощью сосудов и планктонной сети. Макрофиты, моллюски и губки отобраны с помощью бентосного дночерпателя. Определен видовой состав сообществ фитопланктона (31 вид), макрофитов (3), моллюсков (17) и губок (1). Отмечено присутствие токсических диатомовых водорослей Nitzschia longissima, Pseudo-nitzschia delicatissima, Pseudo-nitzschia pseudodelicatissima, Pseudo-nitzschia lineola.
Keywords: algae; macrophyte; porifera; mollusc; coastal; Mediterranean; Turkey